Determination of Isoniazid and Pyridoxine Hydrochloride Levels in Tablets with Ultraviolet Spectrophotometry by Successive Ratio Derivative - Rida Evalina Tarigan; Yustifin Sarumaha (International Archives of Medical Sciences and Public Health, 2022)
Isoniazid and pyridoxine hydrochloride are a combination of anti-tuberculosis drugs that are often used as standard therapy. The advantage of this drug combination is to obtain treatment effectiveness and prevent the emergence of resistance. Examination of the quality of medicinal preparations, determination of the content of efficacious substances is an important part so that a reliable analytical method is needed as well as tools and operational costs that are relatively cheaper, easy to implement, but can provide results with good accuracy and precision. This study aims to determine the levels of isoniazid and pyridoxine hydrochloride in tablet preparations using successive ratio derivative ultraviolet spectrophotometry. isoniazid (10 g/mL) was then transformed into derivative 1 at 4. The results showed that the levels of isoniazid 101.4313% and pyridoxine hydrochloride 104.7125%. Based on the results of the research conducted, it can be concluded that the levels of isoniazid and pyridoxine hydrochloride meet the requirements for levels according to the Indonesian Pharmacopoeia Edition VI.